PENGARUH MINAT DAN KEBIASAAN BELAJAR TERHADAP PRESTASI BELAJAR BAHASA INDONESIA KELAS V SDIT AHMAD YANI - Olivia, Mala; Uswatun Nisa, Hany; Rizki Yono, Robert; Ghufroni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Basic education plays an important role in shaping students' abilities, attitudes, and characters through improving learning achievement. Learning achievement is influenced by various internal factors, especially learning interests and habits. This study aims to determine the effect of learning interests on Indonesian language learning achievement, the effect of learning habits on Indonesian language learning achievement, and the simultaneous influence of both on student learning achievement. The study used a quantitative approach with a causal associative method. The study population was all 27 fifth-grade students of SDIT Ahmad Yani, using a saturated sampling technique. Data collection was carried out through questionnaires to measure learning interests and habits and tests to measure student learning achievement. Data were analyzed using prerequisite tests, descriptive analysis, normality tests, and multiple regression tests. The results of the study showed a positive and significant influence between learning interests on student learning achievement, a positive and significant influence of learning habits on student learning achievement, and a positive and significant influence of interest and learning habits together on Indonesian language learning achievement of fifth-grade students of SDIT Ahmad Yani in the 2025/2026 academic year. Thus, it can be concluded that increasing learning interests and habits makes a real contribution to optimally improving student learning achievement. These results form the basis for teachers to design effective and sustainable learning.